(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
In the 21st century Diabetes mellitus is one of the most challenging health problems. It is one of the important multifactors of commonest metabolic disorders in men and women. Recent epidemiological studies reveal that approximately 246 million of people suffer from diabetes mellitus. By 2025 this figures could be expected to be 380 millions. Its incidence has been estimated to be around 15% of Indian population i.e. 70 million. As per diabetic concerned, WHO has projected India as the leading country in the world and it is epidemic in many developing and newly industrialized nations. It is a major global health problem with diverse causative factors often associated with multiple devastating innervating complications, increasing disability and reducing life expectancy. The information available in the classics of Ayurveda, show that Diabetes mellitus as a disease was very well known to the propounders of Ayurveda. It is amazing to note that the entire knowledge of disease diathesis, prognosis and treatment of diabetes mellitus vis-a-vis Prameha/Madhumeha was equally advanced since antiquity in the classics of Ayurveda. Hence the scientific community and traditional practitioners of all over the world including Ayurveda are in the search of new treatment modalities for better management of Diabetes mellitus. Medicinal plants reveal that plants have enormous therapeutic capabilities for the management of Diabetes mellitus. The present papers deals with medicinal plants with ant diabetic potency which is less known to us and are being used by the traditional healers of North-eastern states. These plants informations have been documented meticulously and have been presented here for further research in the field.